A retrospective observational study on ovarian tumors and analysis of demographic factors and histopathological findings in a tertiary care center, Theni, Tamil Nadu - Priya R; Mahalakshmi Aravazhi; Buvaneshwari K (Asian Journal of Medical Sciences, 2024)
Background: Ovarian cancer is a significant global health concern, ranking 5th among cancer deaths among women and causing more deaths than any other cancer of the female reproductive system. It is the second most common gynecological cancer in India, with a high disease-related mortality rate owing to its asymptomatic nature in the early stages. Aims and Objectives: This retrospective hospital-based observational study aimed to identify the demographic features of women with ovarian tumors detected by ultrasonography and their correlation with histopathology. Materials and Methods: This retrospective hospital-based observational study included 139 women who underwent surgery for ovarian tumors at a tertiary care center in South India between September 2022 and August 2023. Patient details were collected from the gynecological outpatient department, surgical procedures, and final histopathological reports. Descriptive analysis was performed using frequencies and proportions for categorical variables, and the Chi-square test was used to test the statistical significance of the cross-tabulation between categorical variables. Results: Most ovarian tumors were found in multiparous women aged 41–60 years 69 patients, (49.6%), and most were unilateral or cystic. Benign serous cystadenoma was the most common tumor type (n=51, 36.7%), whereas serous cystadenocarcinoma was the most common malignant tumor (n=10, 7.2%). There were statistically significant differences in age group, size, consistency, and laterality according to histopathological examination (P<0.05). Conclusion: This study provides valuable information on the demographic factors and histopathological findings of ovarian tumors in a tertiary care center in South India.